Challenges in gluten-free diet in coeliac disease: Prague consensus - Samasca, Gabriel; Lerner, Aaron; Girbovan, Anamaria; Sur, Genel; Lupan, Iulia; Makovicky, Peter; Matthias, Torsten; Freeman, Hugh J (European journal of clinical investigation, 2017)
BACKGROUND: New treatments in coeliac disease are being vigorously pursued to either replace or facilitate the difficult-tofollow gluten-free diet. DESIGN: The present review intends to summarise the challenges in gluten-free diet adherence during the transitional period, as reflected in the last Prague consensus, published in 2016. RESULTS: The honourable panel members recommended that dietary adherence and the consequences of nonadherence represent key components for discussion in the transitional period setting. CONCLUSIONS: There are numerous difficulties in adhering to gluten withdrawal, but the transition period from adolescence to young adulthood is considered a fragile and high-risk period for intentional and unintentional gluten intake.
Keywords: Diet, Gluten-Free; dietary adherence; Consensus; Humans; biomarkers; gluten-free diet; mladý dospělý; Patient Compliance; childhood; věkové faktory; lidé; konsensus; Adult; Practice Guidelines as Topic; celiakie; bezlepková dieta; Adolescent; směrnice pro lékařskou praxi jako téma; Celiac Disease; Young Adult; Age Factors; adherence pacienta; transition; mladiství